Association of ultra-processed food consumption with cardiovascular risk factors among patients with type-2 diabetes mellitus - Mohammad Heidari Seyedmahalleh; Ensieh Nasli-Esfahani; Mobina Zeinalabedini; Leila Azadbakht (Nutrition & Diabetes)
Abstract Background Ultra-processed foods mainly have high energy content and density and low nutrients. Unhealthy lifestyles mainly develop cardiovascular diseases and, as a result, unhealthy food patterns. Objective This study aimed to investigate the relationship between the consumption of ultra-processed foods (UPFs) and the risk of novel cardiovascular disease (CVDs) in type-2 diabetes mellitus patients (T2DM). Method This is a cross-sectional study that was conducted on 490 type-2 diabetes mellitus patients. A validated 168-item food frequency questionnaire evaluated food intake. Ultra-processed foods were assessed according to NOVA classification. Cardiovascular risk factors such as Castelli risk index 1 and 2 (CRI-I and II), atherogenic index of plasma (AIP), lipid accumulation product (LAP), and cholesterol index (CI) were assessed by traditional CVD risk factors. The anthropometric indices predicting CVD, such as a body shape index (ABSI), body roundness index (BRI), and abdominal volume index (AVI), were assessed. Results Each 20-gram increase in UPF consumption was associated with a significant elevation in serum level of TC [B (SE): 1.214 (0.537); 95% CI: 0.159–2.269] and lower HDL serum concentration [B (SE): −0.371 (0.155); 95% CI: −0.675 to −0.067]. The crude model for CRI 1 [B (SE): 0.032 (0.012); 95% CI: 0.009–0.056], CRI 2 [B (SE): 0.022 (0.009); 95% CI: 0.004–0.040], and AIP [B (SE): 0.006 (0.003); 95% CI: 0.000–0.012] showed significant adverse effects. Conclusions Our study showed that higher consumption of UPFs is associated with higher chances of developing cardiovascular diseases in T2DM patients.